Small Intestinal Cannabinoid Receptor Changes Following a Single Colonic Insult with Oil of Mustard in Mice - Kimball, Edward S.; Wallace, Nathaniel K.; Schneider, Craig R.; D'Andrea, Michael R.; Hornby, Pamela J. (Frontiers in Pharmacology, 2010)
Cannabinoids are known to be clinically beneficial for control of appetite disorders and nausea/vomiting, with emerging data that they can impact other GI disorders, such as inflammation. Post-inflammatory irritable bowel syndrome (PI-IBS) is a condition of perturbed intestinal function that occurs subsequent to earlier periods of intestinal inflammation. Cannabinoid 1 receptor (CB1R) and CB2R alterations in GI inflammation have been demonstrated in both animal models and clinically, but their continuing role in the post-inflammatory period has only been implicated to date. Therefore, to provide direct evidence for CBR involvement in altered GI functions in the absence of overt inflammation, we used a model of enhanced upper GI transit that persists for up to 4 weeks after a single insult by intracolonic 0.5% oil of mustard (OM) in mice. In mice administered OM, CB1R immunostaining in the myenteric plexus was reduced at day 7, when colonic inflammation is subsiding, and then increased at 28 days, compared to tissue from age-matched vehicle-treated mice. In the lamina propria CB2R immunostaining density was also increased at day 28. In mice tested 28 day after OM, either a CB1R-selective agonist, ACEA (1 and 3 mg/kg, s.c.) or a CB2R-selective agonist, JWH-133 (3 and 10 mg/kg, s.c.) reduced the enhanced small intestinal transit in a dose-related manner. Doses of ACEA and JWH-133 (1 mg/kg), alone or combined, reduced small intestinal transit of OM-treated mice to a greater extent than control mice. Thus, in this post-colonic inflammation model, both CBR subtypes are up-regulated and there is increased efficacy of both CB1R and CB2R agonists. We conclude that CBR remodeling occurs not only during GI inflammation but continues during the recovery phase. Thus, either CB1R- or CB2-selective agonists could be efficacious for modulating GI motility in individuals experiencing diarrhea-predominant PI-IBS.